(untitled) (Bangladesh Agronomy Journal, 2020)
An experiment was carried out at the Research Field of Crop Physiology and Ecology Department, Hajee Mohammad Danesh Science and Technology University, Dinajpur from July to November 2018. The study evaluated the effects of poultry litter based composts on morpho-physiological, yield and yield contributing characters of transplanted aman rice (var.Binadhan-7, BRRI dhan56, BRRI dhan66) and soil fertility. The experiment was laid out in a two factorial complete randomized design (CRD) with three replications. Factor A included three varieties (Binadhan-7: V1, BRRI dhan56: V2, and BRRI dhan66: V3) and factor B comprised of three fertilization levels viz. control (inorganic)-F1, poultry litter based compost 20 ton ha-1: F2, and 30 ton ha-1: F3. The performances of plant growth parameters such as plant height, tiller number, leaf number, leaf area, SPAD value, as well as yield and yield contributing parameters, and soil chemical properties were measured. Varieties and fertilizer levels significantly influenced most of the morphophysiological traits and yield and yield contributing characters. The tallest plant was recorded from V2 variety (BRRI dhan56). The highest leaf number hill-1 (80.89 at 30 DAT) was recorded from V3 (BRRI dhan66). The highest number of tiller was produced by the interaction of compost F2 (20 t ha-1) with V1 (Binadhan-7). The highest effective tiller number (13.67) hill-1wasrecorded from F2 (compost 20 t ha-1) with F1 (Binadhan-7) at maturity. The longest panicle (24.16 cm) was found in F1V1 (inorganic with Binadhan-7) treatment. The highest 1000-grain weight (23.57 g) was recorded from F3V3 treatment (compost-30 t ha-1 with BRRI dhan66). The maximum harvest index was recorded from F1 (inorganic) with BRRI dhan66. Soil fertility status increased with higher dose poultry litter based compost (30 t ha-1). Bangladesh Agron. J. 2020, 23(1): 13-27